Investitionen: Warum wir sie brauchen und wie wir sie kriegen; Blessed is he who expects nothing? The role of expectations for investment - Michael Christl; Monika Köppl-Turyna; Hanno Lorenz (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
Dieser Beitrag untersucht den Zusammenhang zwischen Investitionswachstum, Zinsen und Erwartungen fur̈ Österreich. Basierend auf einem Panel von 73 Wirtschaftssektoren zeigt sich, dass Zinsänderungen nur dann einen positiven Einfluss auf Investitionswachstum haben, wenn die Erwartungen stark zuruc̈kgehen. Sind die Erwartungen konstant (gut oder schlecht), so haben Zinsen jedoch kaum einen Einfluss. Ebenso zeigt sich, dass stark steigende Erwartungen einen positiven Effekt auf das Investitionswachstum aufweisen. Außerdem geht ein Anstieg der Produktionsbesteuerung sowie stärkere Kapitalmarktregulierung mit einem negativen Investitionswachstum einher. – – This article focuses on the relationship between investment growth, interest rates and economic expectations. Using a panel based on 73 sectors of the Austrian economy, we show that a reduction in the interest rate is associated with positive investment growth, but only if expectations decrease. If expectations remain stable, decreasing interest rates has no effect on investment growth. An increase in expectations is associated with higher investment growth. Additionally, we show that higher taxation on production as well as increasing capital market regulation tend to decrease investment growth.
Keywords: E22; E43; E66; H32; 330; investment; interest rate; expectations; Austria